Modeling nearshore processes in UMS : Coastal area of Sepanggar Bay - Md. Azharul Hoque; Ejria Saleh (Universiti Malaysia Sabah, 2007)
Nearshore coastal environment in UMS coastal area of Sepanggar bay has been studied through extensive field measurements and model calculations. The study covers the spatial and monsoonal variations of wave climate, water current velocity, suspended sediment concentration, temperature salinity, dissolved· oxygen (DO), water transparency, pH, plankton communities and macrobenthos assemblages in the study area. Effects of cage culture and harmful algal bloom have also been investigated. Samples were collected from five sampling stations covering nearshore area, cage culture area and offshore area of the study area covering northeast monsoon, inter-seasonal monsoon and southwest monsoon. Wave dynamics were studied through model calculations using JONSWAP spectral method.Temperature, salinity, pH and dissolve oxygen concentration were measured in situ using an YSI meter. Aquadrop profiler was used to measure the current velocity. Water transparency was measured using a Secchi disc. Total suspended solids of collected water samples were determined in the laboratory using the drying, burning and weighing method. Phytoplankton and zooplankton were collected using a 20llm mesh sized plankton net. Grab sampler were used to collect the macrobenthos. A significant seasonal variations were observed in the physical water properties while the differences for spatial variation were found to be statistically insignificant. However, field measurements showed lower velocity in inside cage area which is due to the cage structure. As consequences, the suspended solids were found higher in inside cage when compared to nearshore and offshore areas. Phytoplankton number, abundance and different diversity values showed significant temporal variation (except Margalefs Richness Index) while no significant differences were observed in the spatial distribution of phytoplankton. For zooplankton, significant temporal variation was observed only for Pielou Evenness Index and Margalefs Richness Index. No significant spatial' distribution was observed for number, abundance and different diversity values of the zooplankton community. Macrobenthos assemblage showed significant variations both for the temporal and spatial distribution of the number, abundance and different diversity values. Findings of the present study indicate that there is no signi ficant effect of cage culture in the study area. Physical water properties (Temperature, salinity, DO, pH, water transparency) and phytoplankton assemblage during red tide duration were found to be significantly different than those during non red tide duration.